Estratégias de seleção de materiais para viseiras de goleiro de hóquei - Bernardo, Diandra (Universidade Federal de São Carlos, 2024)
Visors for goalkeeper helmets are a relevant topic for hockey players, since access is made difficult by the lack of supply in the national territory, which results in a high cost for players. Due to the great mechanical stress suffered in a game situation, as well as shocks with the game ball and sticks, the ideal material must present excellent impact resistance and flexural rigidity, ensuring durability for the visor and safety for the user, in addition to have high hardness, being responsible for minimizing surface scratches that reduce the visibility and consequently the usefulness of the product. In addition to optimized mechanical performance, transparency and processability constraints need to be considered. Therefore, the material selection analysis aiming at cost reduction must consider multiple constraints, making it essential to use decision-making theories. Thus, using the TOPSIS and COPRAS methodologies, combined with the Saaty weighting methodologies that takes into consideration the preferences of goalkeeper visor users, and entropy weighting, a mathematical method that objectively indicates the weighting factors for each criterion according to the diversification of values within a group of properties, selection was carried out by ranking the potential candidates. This work aimed to indicate polymeric materials that have the best synthesis of expected characteristics according to each selection method. As a result, it was concluded that the choice of selection method did not impact the result as much as the weighting method. PCTA was chosen as the best material candidate among those analyzed.
Material selection strategies for hockey goalkeeper visors
Keywords: Viseiras de goleiro; Seleção de materiais; TOPSIS; COPRAS; Saaty; Entropia; Visors for goalkeepers; Materials selection; Entropy; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS